An Underactuated Multi-finger Grasping Device. (17th February 2014) - Rossi, Cesare; Savino, Sergio
In this paper, a mechanical model for an underactuated multi-finger grasping device is presented. The device has single-tendon, three-phalanx fingers, all moved by only one actuator. By means of the model, both the kinematic and dynamical behaviour of the finger itself can be studied. The finger is part of a more complex mechanical system that consists of a four-finger grasping device for robots or a five-finger human hand prosthesis. Some results of both the kinematic and dynamical behaviour are also presented.